Formacja katechetów w aspekcie kanonicznym - Adamczyk, Jerzy (Poznańskie Studia Teologiczne, 2014)
The article first presents the need and necessity of the formation of catechists. Then it shows the issue of the subject responsible for the preparation of catechists. There is also a lengthy discussion of the character and contents of instruction offered to catechists, both in the basic and the ongoing formation. The last paragraph is devoted to schools for catechists.